Forecasting of Life Threatening Arrhythmias Using the Compression Entropy of Heart Rate - Baumert, M.; Baier, V.; Haueisen, J.; Wessel, N.; Meyerfeldt, U.; Schirdewan, A.; Voss, A. (Methods of Information in Medicine, 2004)
Objectives: Ventricular tachycardia (VT) provoking sudden cardiac death (SCD) are a major cause of mortality in the developed countries. The most efficient therapy for SCD prevention are implantable cardioverter defibrillators (ICD). In this study heart rate variability (HRV) measures were analyzed for short-term forecasting of VT in order to improve VT sensing and to enable a patient warning of forthcoming shocks.Methods: The last 1000 normal beat-to-beat intervals before 50 VT episodes stored by the ICD were analyzed and compared to individually acquired control time series (CON). HRV analysis was performed with standard parameters of time and frequency domain as suggested by the HRV Task Force and furthermore with a newly developed and optimized nonlinear parameter that assesses the compression entropy of heart rate (Hc).Results: Except of meanNN (p = 0.02) we found no significant differences in standard HRV parameters. In contrast, Hc revealed highly significant (p = 0.007) alterations in VT compared with CON suggesting a decreased complexity before the onset of VT.Conclusion: Compression entropy might be a suitable parameter for short-term forecasting of life-threatening tachycardia in ICD.
Keywords: Implantable cardioverter defibrillators; heart rate variability; nonlinear dynamics